ANALISIS DISKONTO DAN NILAI WAKTU UANG DALAM PERSPEKTIF KEUANGAN SYARIAH - Lailiyah Najma Zahira; Dessy Boegiyati (Cashless : Journal of Sharia Finance and Banking, 2026)
This research aims to reconstruct the concept of the time value of money from a Sharia perspective by developing the Economic Value of Time (EVT) as an alternative to the riba-based conventional Time Value of Money (TVM). Utilizing a mixed-method approach that combines qualitative and quantitative analysis through systematic literature review and comparative-mathematical analysis, this study formulates the Integrated Sharia Discounting Model Framework (KMDST) applied to murabahah, ijarah, syirkah, and sukuk instruments. The findings indicate that Sharia discounting mechanisms can be independently transformed by substituting interest variables with real return indicators such as margins, ujrah, and the Expected Rate of Return (ERR). Quantitative simulation results on an IDR 800,000,000 financing scenario demonstrate a mathematical convergence phenomenon, where the NPV of both Sharia and conventional systems yields an identical figure of -IDR 6,950,127 at the same discount rate. The study concludes that while methodologically accurate and precise, Islamic finance possesses a substantial advantage in terms of risk-sharing and economic justice, which are absent in conventional systems. Practically, this model provides guidance for financial institutions in determining discount rates aligned with real-sector productivity and Sharia compliance.